A situational analysis of pool car management : the Department of Water Affairs and Forestry, Limpopo Province - Malatji, Masadiki Violet (University of Limpopo (Turfloop Campus), 2008)
Despite crucial strategic value of fleets, most organizations have relegated the management of their vehicles as being very low on their list of priorities. Consequently, they are entrusting unsuitable people with management of their fleet. Without proper management, huge amounts of money are wasted through fuel fraud and with repairs being done too late or not at all, leaving expensive vehicles idle for months (Barrow 1999).It has been observed that managing fleets with the emphasis on bookkeeping and finance, rather than operational realities, leads to huge and unnecessary costs and massive fraud (Barrow 1998). Efficiency in fleet management is about having a fleet that works directly to support the organizational goals. It is imperative that a study was conducted to analyze the situation of pool cars in the Department of Water Affairs and Forestry (DWAF) in the Limpopo Province to ensure the efficiency in its fleet management
Thesis (MBA) --University of Limpopo, 2008
Keywords: Pool car management; 388.143212068; Car pools; Motor vehicles fleets